The interaction effects between depression and sleep status on asthma: a national cross-sectional study - Lai, Yuxin; Zhang, Xiaomei; Dong, Huan; Li, Mengqian (Frontiers in Psychiatry, 2024)
Background: Asthma, depression, and sleep problems are three significant public health issues that are closely interrelated. This study aims to explore the relationship between depression, sleep status and asthma, as well as the potential interaction among these conditions and their effects on asthma. Method: This cross-sectional study utilized data from the 2005-2008 National Health and Nutritional Examination Survey, including information on asthma, depression, sleep status and confounding factors. Multivariate logistic regression analyses were conducted to investigate the relationship between depression, sleep status, and asthma. Subgroup analyses were conducted to test the p-interaction between depression and each stratified variable.Additionally, both multiplicative and additive approaches were employed to assess the interaction between depression and sleep status on asthma, as well as to quantify their combined effects. Results: A total of 8,327 participants (mean age 46.53) were included in this study. Compared to the individuals without depression, those with depression have an increased risk of asthma [OR = 1.57, 95%CI = 1.22-2.03], and an increase in the severity of depressive symptoms is associated with a higher risk of developing asthma. Additionally, poor sleep quality, sleep disorders, and insufficient sleep was associated with an increased risk of asthma. Effect modification was observed between depression and PIR status, smoking status, and sleep disorders in relation to asthma (p-interaction <0.05).Moreover, we found a positive interaction between severe depression and excessive sleep (OR = 29.07, 95% CI = 3.24-260.38). Furthermore, we observed the quantitative additive interaction indicators between moderately severe depression and insufficient sleep [RERI = 1.63, 95%CI = 0.18-3.83; AP = 0.51, 95%CI = 0.15-0.87; SI = 3.92, 95%CI = 1.65-23.50] influencing asthma risk. Conclusion: Our study revealed distinct associations between depression, the severity of depressive symptoms, poor sleep quality, sleep disorders, and insufficient sleep with asthma. Additionally, there was an interaction between moderately severe depression and insufficient sleep on asthma. Psychological and sleep assessment are essential in asthma management. Clinicians should consider the potential risk of depression and sleep problems in asthma patients and intervene. Further longitudinal research is needed to better understand the pathophysiological mechanisms behind the interactions between asthma, depression, and sleep problems.